2004
DOI: 10.1021/cm048433e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanostructured Li[Ni1/3Co1/3Mn1/3]O2 via a Modified Carbonate Process

Abstract: Li[Ni1/3Co1/3Mn1/3]O2 synthesized via the modified carbonate process showed a homogeneous particle distribution with 10-μm secondary particles. Higher discharge capacity was retained even at 10 C (2800 mA g-1). This superior high rate capability would be mainly due to the well-controlled synthesis process, thus the morphology and its effects on electrochemical properties are significantly reproducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…2(a), the Li[Ni 1/3 Co 1/3 Mn 1/3 ]O 2 powder prepared by the improved carbonate co-precipitation method has a spherical morphology, and the secondary particle is composed of small primary particles. The morphology of the prepared sample is similar to previous reports [13]. By contrast, the sample prepared by the conventional carbonate co-precipitation method ( Fig.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…2(a), the Li[Ni 1/3 Co 1/3 Mn 1/3 ]O 2 powder prepared by the improved carbonate co-precipitation method has a spherical morphology, and the secondary particle is composed of small primary particles. The morphology of the prepared sample is similar to previous reports [13]. By contrast, the sample prepared by the conventional carbonate co-precipitation method ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…This results in the spherical Li Fig. 6., The capacity retention after fifty charge-discharge cycles of prepared by the improved carbonate co-precipitation was 162 mAh g −1 and 96.6% of the initial discharge capacity was retained after 50 charge-discharge cycling, which is a little better than previous reports [13].…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…capability, better power retention and better capacity retention so that the size of the battery pack can be minimized accordingly. This objective was being approached with several reported strategies including (a) developing advanced electrode materials with better power capability and cycling performance [5][6][7][8];…”
Section: Introductionmentioning
confidence: 99%
“…It was found that increasing the microwave radiation temperatures raised the retention of LiNi 1/3 Co 1/3 Mn 1/3 O 2 powders at the same cycle. The reason for the increase in retention is that particles with a less-agglomerated morphology would adapt volume changes involving structural transition or intercalation of lithium ions [45]. The coulomb efficiency of SP25, SP100, SP130 and SP180 after 10 cycles is also listed in Table 1.…”
Section: Electrochemical Characterizations Of Lini 1/3 Co 1/3 Mn 1/3 Omentioning
confidence: 99%